2022
DOI: 10.1111/mpp.13276
|View full text |Cite
|
Sign up to set email alerts
|

HpaP divergently regulates the expression of hrp genes in Xanthomonas oryzae pathovars oryzae and oryzicola

Abstract: The bacterial pathogens Xanthomonas oryzae pathovars oryzae (Xoo) and oryzicola (Xoc) cause leaf blight and leaf streak diseases on rice, respectively. Pathogenesis is largely defined by the virulence genes harboured in the pathogen genome. Recently, we demonstrated that the protein HpaP of the crucifer pathogen Xanthomonas campestris pv. campestris is an enzyme with both ATPase and phosphatase activities, and is involved in regulating the synthesis of virulence factors and the induction of the hypersensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…actinidiae ( 93 ). Recently, Li et al ( 94 ) reported similar results in XVM2 medium, where the expression of hrp genes was decreased in Xanthomonas campestris pv. campestris ( Xcc ) hpaP deletion mutant.…”
Section: Discussionmentioning
confidence: 59%
“…actinidiae ( 93 ). Recently, Li et al ( 94 ) reported similar results in XVM2 medium, where the expression of hrp genes was decreased in Xanthomonas campestris pv. campestris ( Xcc ) hpaP deletion mutant.…”
Section: Discussionmentioning
confidence: 59%
“…HR was tested on Nicotiana benthamiana leaves, as previously described [ 5 ]. Following a similar procedure, Xoc cells from cultures were washed and resuspended in sodium phosphate buffer (SPB, 5.8 mM Na 2 HPO 4 and 4.2 mM NaH 2 PO 4 , pH 7.0) to an OD 600 of 0.5 (5 × 10 8 CFU/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Extracellular-polysaccharide (EPS) and extracellular-enzyme assays were conducted, following previously established protocols [ 4 , 5 ]. For EPS production analysis, the Xoc strain was spotted on NA plates supplemented with 2% sucrose and incubated for 3 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations